(untitled) (Mustansiria Dental Journal, 2019)
Objective. Current study was aimed to evaluate the activity of biosurfactants and other cleansing solutions of the acrylic resin on growth of Candida albicans and Streptococcus mutans. Study design. Heat cure acrylic resin discs were prepared and precoated with four types of liquids: water, biosurfactant, chlorhexidine mouth wash and denture cleanser. The water was used as control. The discs kept in the solutions overnight after that the antimicrobial assay was tested against Candida albicans and Streptococcus mutans. Also reduction of growth and biofilm formation of C. albicans on denture acrylic discs was tested by using biosurfactant. Results. Precoating with biosurfactant caused a greater inhibition in the growth of both types of the microorganisms than chlorhexidine and denture cleanser, with inhibition zone diameter 25mm and 15mm against Streptococcus mutans and Candida albicans respectively , 96 % of Candida albicans growth reduction on denture acrylic discs. Also biosurfactant showed reduction in biofilm formation of Candida albicans on denture acrylic discs. Conclusions. This study demonstrated that biosurfactant was the best preventive agent for acrylic resin compared with other mouth washer and denture cleanser.